Socio-geographic changes in small island communities - the example of the Island of Zlarin - Sanja Klempić Bogadi; Sonja Podgorelec (Geoadria, 2011)
On the example of the island of Zlarin, the authors investigate fundamental socio-geographic processes and the most important changes in the way of life of communities on small Croatian islands from 1970s until today. This paper presents a part of the results of a study conducted in February 2011 on Zlarin, within the framework of researching the quality of life of the population on the islands of Šibenik. It presents partial results of research on the quality of life of the population of Zlarin which was conducted using questionnaire and observation methods on a sample of 67 respondents. The results show that, due to their desire to assure the demographic survival of their community, Zlarin islanders are increasingly opening up towards foreigners – first of all to immigrants, and then to tourists, in whom they place their hopes for demographic and economic revitalisation. However, the islanders still show a strong sense of affiliation to their relatively homogeneous and intimate island community, to which they still have a strong sense of belonging.